2009
DOI: 10.1080/10739680903298228
|View full text |Cite
|
Sign up to set email alerts
|

Event-Tracking Model of Adhesion Identifies Load-Bearing Bonds in Rolling Leukocytes

Abstract: Objectives-P-selectin binding to P-selectin glycoprotein ligand (PSGL)-1 mediates leukocyte rolling under conditions of inflammation and injury. The objectives were to develop an efficient, high temporal resolution model for direct simulation of leukocyte rolling, and then to conduct a study of load-bearing bonds using the model. Methods-A stochastic π-calculus-driven Event TrackingModel of Adhesion was developed and compared with experimental data. Multiple simulations for each case were conducted to obtain h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…qDF microscopy is an adaptation of TIRFM, allowing realtime measurements of ''height'' of the hills and valleys in the footprint of rolling neutrophils. qDF revealed that a rolling neutrophil has a fourfold larger footprint than that predicted by theoretical models [39,40] as well as in vivo measurements [12,18]. In addition, qDF revealed three to four long tethers at the rear of each rolling neutrophil.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…qDF microscopy is an adaptation of TIRFM, allowing realtime measurements of ''height'' of the hills and valleys in the footprint of rolling neutrophils. qDF revealed that a rolling neutrophil has a fourfold larger footprint than that predicted by theoretical models [39,40] as well as in vivo measurements [12,18]. In addition, qDF revealed three to four long tethers at the rear of each rolling neutrophil.…”
Section: Introductionmentioning
confidence: 77%
“…Over the last two decades, P-selectinmediated neutrophil rolling has been studied in vivo using intravital microscopy [8,12,56] and in in vitro flow chambers using trans-illumination [1,28,59], epifluorescence [50], and DIC microscopy [42,47]. These studies have provided cellular and molecular measurements that have led to the creation of in silico theoretical models [7,25,27,39,40], which provide invaluable insight into the molecular and cellular mechanisms that govern neutrophil rolling.…”
Section: Introductionmentioning
confidence: 99%
“…The time interval ∆t of 10µs is used, as suggested by Ref. (20), to simulate leukocyte rolling for a period of 3s. All parameters used in the AD are presented in Table 1 and Table 2.…”
Section: Adhesive Dynamicsmentioning
confidence: 99%
“…This idea was first proposed by Shao et al (18). Pawar et al (19) (20,21). However, these studies were limited to microvillus extensional deformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation